Predictors of Dropout From Cognitive-Behavioral Group Treatment for Panic Disorder With Agoraphobia: An Exploratory Study. (January 2017) - Bélanger, Claude; Courchesne, Catherine; Leduc, Andrea G.; Dugal, Caroline; El-Baalbaki, Ghassan; Marchand, André; Godbout, Natacha; Marcaurelle, Roger; Perreault, Michel
Panic disorder and agoraphobia are both characterized by avoidance behaviors, which are known correlates of treatment discontinuation. The aim of this exploratory study is to distinguish the profile of participants suffering from panic disorder with agoraphobia that complete treatment from those who discontinue therapy by assessing four categories of predictor variables: the severity of the disorder, sociodemographic variables, participants' expectations, and dyadic adjustment. The sample included 77 individuals diagnosed with panic disorder with agoraphobia who completed a series of questionnaires and participated in a cognitive-behavioral group therapy consisting of 14 weekly sessions. Hierarchical linear regression analyses revealed the importance of anxiety, prognosis, and role expectations as well as some individual variables as predictors of therapeutic dropout, either before or during treatment. Among the most common reasons given by the 29 participants who discontinued therapy were scheduling conflicts, dissatisfaction with treatment, and conflicts with their marital partner. These results suggest that expectations and dyadic relationships have an impact on therapeutic discontinuation. The clinical implications of these findings are discussed.